2018
DOI: 10.1021/acs.jpcc.8b01324
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Superiority of the Marcus–Hush Electrode Kinetic Model in the Electrochemistry of Dissolved Decamethylferrocene at a Gold-Modified Electrode by Fourier-Transformed Alternating Current Voltammetry

Abstract: Fourier-transformed alternating current (AC) voltammetry is used to compare the applicability of the Butler−Volmer (BV) and Marcus−Hush (MH) models of electrode kinetics (k 0 ) to an outer-sphere electrode process where both oxidized and reduced species are soluble. According to numerical simulations, differences between the two models can be revealed clearly by analysis of the AC harmonics when the values of k 0 and reorganization energy are sufficiently small. Experimentally a Au electrode coated with a self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Thus, the 'odds' for each model being compared are updated as more information becomes available. We have used this 'updating the odds' approach by treating each of the harmonics obtained in an AC voltammetric experiment as providing new information [40] and confirmed that use of the Marcus-Hush model is superior for one particular electrode process [40] where this had been suggested previously on the basis of analysis by conventional data optimisation [41]. Intriguingly, even though the attributes of computersupported data analysis in DC voltammetry have been established and even reviewed by Speiser [42], the importance of quantifying confidence limits and reporting parameter estimates emanating from a comparison of experimental and simulated data seems to be absent as a routine aspiration in voltammetry.…”
supporting
confidence: 62%
“…Thus, the 'odds' for each model being compared are updated as more information becomes available. We have used this 'updating the odds' approach by treating each of the harmonics obtained in an AC voltammetric experiment as providing new information [40] and confirmed that use of the Marcus-Hush model is superior for one particular electrode process [40] where this had been suggested previously on the basis of analysis by conventional data optimisation [41]. Intriguingly, even though the attributes of computersupported data analysis in DC voltammetry have been established and even reviewed by Speiser [42], the importance of quantifying confidence limits and reporting parameter estimates emanating from a comparison of experimental and simulated data seems to be absent as a routine aspiration in voltammetry.…”
supporting
confidence: 62%
“…35,36 We have previously reported the use of FTACV to assess the applicability of the BV and MH models by studying the electrode kinetics of the DmFc 0/+ process in propylene carbonate at an octanethiolmodified Au electrode. 21 On the basis of the LS analysis, the MH model (LS = 94.3%) was shown to provide better agreement with the experimental data than the BV model (LS = 76.5%). However, comparison of LS values does not provide information on exactly how preferential the MH model is relative to the BV one.…”
Section: Analytical Chemistrymentioning
confidence: 91%
“…Summary of the Bayesian Analysis Protocol Applied to MH and BV Models for Oxidation of DmFc in Propylene Carbonate at a Gold-Modified Electrode21 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43] In brief, a single barrel micropipette was pulled to ≈50 µm tapered end, filled Theory-experiment comparison. Since negligible differences are expected between Butler-Volmer (BV) and Marcus-Hush theories in simulations when the electron transfer kinetics are relatively fast, as applies to the Fc 0/+ process studied in this paper, 44 the simpler BV theory was used in all simulations. Simulating the simple one-electron transfer reaction given in Equation…”
Section: Electrochemical Droplet Cell Measurements Local Electrochemmentioning
confidence: 99%